Developing an e-Module about Sound Waves with a STEM Approach to Improve Students' Critical Thinking Skills - Aslamiyah Rambe; Syahruddin Aritonang; Malika Ritonga; Nur Hasanah (Universitas Pendidikan Mandalika, 2026)
The integration of information and communication technology (ICT) into education has encouraged the development of innovative learning resources, particularly electronic modules (e-modules), to support interactive and independent learning. Physics, despite its fundamental role in fostering analytical and critical thinking, is often perceived as abstract and difficult, with conventional instruction limiting student engagement and higher-order thinking. To address these challenges, this study developed a STEM-based e-module on sound waves aimed at enhancing students' critical thinking skills. This study employed a 4D development model—define, design, develop, and disseminate—with 34 11th-grade students from SMAN 6 Padangsidimpuan as participants. Instruments included expert validation (content, media, and language), teacher and student questionnaires, and a pretest-posttest assessment of critical thinking. This electronic module achieved a validity score of 96.66% (very valid), a practicality rating of 96.36% from teachers and 85.95% from students (very practical), and effectiveness was demonstrated by a significant increase in students' posttest scores (M = 85.59) compared to pretest scores (M = 36.76), exceeding the minimum competency. The results of the paired t-test showed t = 17.89 and df = 33, p < 0.001, with a very large effect size (Cohen's d = 3.26). The results of the study show that the use of STEM-based e-modules is effective in improving students' critical thinking skills. Results dissemination shows involvement of active students and ability adaptation across the board. These findings confirm that this STEM -based electronic module is valid, practical, and effective, and provides an innovative solution to support critical thinking, problem-solving, and technological literacy in 21st-century physics education.